Hold five lines strategy to manage two key points to prevent hospital-acquired infection through ultrasound visualization technology - Yin, Wanhong; Wei, Ying; Su, Jing; Tie, Xin (Frontiers in Medicine, 2025)
With advancements in medical technology, the management of critically ill patients has significantly improved. However, the incidence of hospital-acquired infection in intensive care unit (ICU) settings has also increased. These infections not only negatively impact patient prognosis but also waste valuable medical resources. Impaired barrier function and increased local bacterial load, resulting from five primary pathways, are two key points in hospital-acquired infections. Point-of-care ultrasound (POCUS) enables the visualization of secretion accumulation and barrier damage, providing guidance for clinical interventions to restore the barrier and clear microorganisms. This technology also allows for the early detection of potential risks that could lead to hospital-acquired infections, enabling timely preventive measures. Therefore, we propose five-line principles for hospital-acquired infection prevention and control and discuss how POCUS can guide their implementation, aiming to provide a structured reference for clinical practice.